Mães fora do armário: travessias de re(existências), negações, conflitos e lutas - Fonseca, Sandra Teixeira da (Universidade Federal de São Carlos, 2021)
The research analyzed life stories of mothers of transgender people who came out of the closet, that is, who publicly take on the trans identity of their sons and daughters and the social and political struggle in front of a cisnormative society that, despite the achievements of the transgender community , the markers of cisnormativity and heteronormativity still continue to regulate the existence of bodies of their daughters and sons. To achieve the research objective, five interviews were conducted from the perspective of oral history with mothers of transgender people who live in the cities of Campinas / SP and Sorocaba / SP and who participate in movements and actions for the rights of trans people. The categories family and transsexuality were analyzed, making an excerpt in their memories of the themes of childhood, education and gender transition. The results showed that the acceptance of these mothers to the transgenderity of their daughters and sons, breaking political, social and religious “norms” that challenged them, are the result of affections, the search for knowledge about gender identity issues and the collective involvement with other mothers of transgender people and with institutions fighting for rights and respect for the LGBTQIA + community (Lesbians, Gays, Bisexuals, Transvestites and Transsexuals, Queers, Intersexes, Asexuals and other groups and variations of sexuality and gender. It is concluded that the five mothers who came out of the closet in favor of the struggle for the legitimacy of the existence of their transgender daughters and sons, came to welcome them and them through a process of constant search to find out about gender and sexuality issues, through references sought in collectives , NGOs and even small groups of mothers of LGBTQIA + people. Childhood, education and gender transition are fundamental categories and n the entire process, as they constitute transgender subjects and subjects. The collectivity of mothers makes a difference in the process of welcoming daughters and sons by these mothers. But, in the end, it is looking and listening, as the formation of a network of affections, that show the main keys to make a difference about differences.
Mothers Outside the Closet: crossings of re(existences), denials, conflicts and struggle
Keywords: transexualidade; história oral; mãe; armário; educação; transsexuality; oral history; mother; cabinet; education; CIENCIAS HUMANAS::EDUCACAO